049. Massive pulmonary embolism and deep vein thrombosis associated with elevated plasma levels of factor VIII - Ampelidou, Varvara (J Thorac Dis, 2015)
BACKGROUND: The association between elevated plasma coagulation factor VIII (FVIII) levels and Venous Thromboembolism (VTE) was first described in the Leiden Thrombophilia Study. Until today the measurement of FVIII levels is not included in laboratory investigation of possible congenital thrombophilia in cases of unexplained VTE. Nevertheless, FVIII levels above 150% seemed to be correlated with high risk of VTE. CASE REPORT: We present a case of a 53-year-old female patient who was admitted to the National Health System Pulmonary Department of “G. Papanicolaou” Hospital of Thessaloniki because of massive pulmonary embolism. Diagnosis was confirmed with a positive computed tomography angiography and the patient was started on low molecular weight heparin. An ultrasonography of deep leg veins showed extensive deep vein thrombosis. The patient had no identifiable secondary hypercoagulable conditions (among which no antiphospholipid syndrome or malignancy) so the search was extended towards hereditary thrombophilia. No one abnormality of antithrombin, protein C or S, factor V Leiden mutation, prothrombin gene mutation G20210A, dysfibrinogenemia or hyperhomocysteinemia was uncovered. The only abnormality was the significant increase in the plasma levels of FVIII, which was measured at 383%. CONCLUSIONS: Correlation of increased levels of FVIII to VTE risk, its role in recurrent thrombosis and its engagement in the pathophysiology of chronic thromboembolic pulmonary disease are discussed. Factor VIII assay should be considered in the work-up of idiopathic, recurrent VTE as well as the need of long-term anticoagulation therapy.